The Effect of Plasma-Treated Boron Nitride on Partial Discharge Characteristics of LDPE - N.A Awang; M.H Ahmad; Y.Z. Arief; I.H. Zakaria; N.A. Ahmad (Institute of Advanced Engineering and Science, 2017)
Power supply reliability is a key factor in a country economic stability. It is contributed by the reliable power distributor via transmission lines, overhead or underground cables. However, the power cables and accessories are always exposed to pre-breakdown phenomena known as partial discharges (PD) which commonly occur in microvoids, defects or protrusions inside the insulation. To improve the performance of the cable insulation against PD, nanofillers are added into the insulating materials. However, to achieve superior performance of PD resistance, the nanofillers must be homogeneously dispersed into the polymer matrices with tightly bonded interfacial zones. Therefore, this could be achieved by employing method of surface functionalization by using cold atmospheric plasma to strengthen the filler/polymer interfaces. In view of foregoing, this study investigated the effects of surface treated boron nitride (BN) nanoparticles in Low Density Polyethylene (LDPE) on the PD characteristics by following CIGRE Method II at 7 kVrms applied voltage. The phase resolved PD characteristics were performed. The results revealed that by treating the nanofillers with cold plasma, the PD resistance of LDPE were highly achieved compared with the untreated BN nanofillers.